The Relationship Between Home Sanitation and Diarrhea In Toddlers In The Work Area Of The Lempake Health Center Samarinda City - Rosdiana; Suhartini; sumadi (Universitas Widya Gama Mahakam Samarinda, 2023)
Objectives: To determine the relationship between home sanitation and the incidence of diarrhea in toddlers in the working area of the Lempake Community Health Center, Samarinda City in 2023. Research Metodes: Quantitative method with cross sectional research design. The research sample was toddlers who had experienced diarrhea with a sample size of 79 respondents. The sampling technique uses purposive sampling technique. Data analysis in the study used the Chi-Square statistical test. Results: The results showed that there was a relationship between latrine cleanliness and the incidence of diarrhea P-value (0,009 < 0,05), there was a relationship between waste management and the incidence of diarrhea P-value (0,046 < 0,05), there was no relationship between the type of floor of the house and the incidence of diarrhea in toddler P-value 90,230 > 0,05). Conclusion: There is a relationship between latrine cleanliness of latrines and the incidence of diarrhea in toddlers with a P-value (0,009 < 0,05), there is a relatonship between waste management and the incidence of diarrhea in toddlers with a significance P-value (0,046 < 0,05), there is no relationship between the type of floor of the incidence of diarrhea in toddlers with a significant P-value (0,230 > 0,05).